QUIZALOFOP-P-ETHYL CONTROLLING SOURGRASS (Digitaria insularis) AND GOOSEGRASS (Eleusine indica) IN INFESTED COFFEE AREAS - Vilela, Ximena Maira de Souza; Medeiros, Fernanda Carvalho Lopes de; Gonçalves, Adenilson Henrique; Silva, Lindomar Canuto da (Coffee Science - ISSN 1984-3909, 2019)
Chemical control is the main weed management system in coffee crop. Herbicides alternatives controlling grass weeds in infested coffee areas are limited, mainly due to the few options of registered herbicides. Thus, it is important to evaluate selective post-emergence herbicide to control these important weeds in coffee crop. The objective of this work was to evaluate the selectivity, efficiency and agronomic viability of the herbicide IHH 0513 (Quizalofope-P-ethyl 50g ai L-1) compared to Glyphosate on grass control in coffee crop. Two experiments were carried out in randomized blocks with four replications in the municipality of Lavras and Santana da Vargem (MG - Brazil) in a commercial coffee crop cultivar “Mundo Novo” and “Catuai” to evaluate the herbicide effectiveness in the crop rows. The experimental design was a randomized block design with seven treatments and four replications. Treatments consisted of IHH 0513 doses (Quizalofope-P-ethyl 25, 50, 75 and 100 g ai ha-1) compared to the standard GLI OVER (Glyphosate 480 g ia L-1) at the dose of 1680g ai ha-1 + Iharol at 0.5% v/v. Application occurred when sourgrass and goosegrass were at the beginning of development with up to 4 tillers (early vegetative stage) and in a second trial, at advanced stages of development (highly branched and /or flowering). Control assessments in percentage were performed at 7, 14, 21 and 28 days after application (DAA) of the treatments. A note of phytotoxicity was given by the EWRC scale (1964). The control of weeds was evaluated in each experimental plot using the visual notes scale of FRANS et al. (1986), where: 0% represents no control, and 100% total control of the species in question, compared to the population present in the non-weed control. In general, the dose of 1500 and 2000 mL per hectare of IHH 0513 (75 and 100 g ai ha-1) for the weeds at early vegetative stage presented the highest levels of controls (above 90%). The dose of 2000 mL per hectare (100 g ai ha-1) was efficient at 28 DAA to control more developed plants. No symptoms of phytotoxicity caused by the IHH 0513 product were detected at any dose tested. Quizalofop-P-ehtyl can be recommended for integrated weed management in coffee for sourgrass and goosegrass.